2014
DOI: 10.1016/j.taap.2014.08.027
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosyl-l-methionine protection of acetaminophen mediated oxidative stress and identification of hepatic 4-hydroxynonenal protein adducts by mass spectrometry

Abstract: Acetaminophen (APAP) hepatotoxicity is protected by S-adenosyl-L-methionine (SAMe) treatment 1 hour (h) after APAP in C57/Bl6 mice. This study examined protein carbonylation as well as mitochondrial and cytosolic protein adduction by 4-hydroxynonenal (4-HNE) using mass spectrometry (MS) analysis. Additional studies investigated the leakage of mitochondrial proteins and 4-HNE adduction of these proteins. Male C57/Bl6 mice (n=5/group) were divided into the following groups and treated as indicated: Veh (15 ml/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…These processes, in turn, limit the apoptotic potential of HNE [2,20,30]. HNE detoxification by GSTs can be reduced due to depletion of GSH, which in turn may lead to increased levels of HNE [31,32]. On the other hand, S-adenosyl methionine (SAM) diminishes HNE modification of enzymes which have a vital role in the detoxification of HNE [32].…”
Section: Hne Reactivity and Metabolismmentioning
confidence: 99%
“…These processes, in turn, limit the apoptotic potential of HNE [2,20,30]. HNE detoxification by GSTs can be reduced due to depletion of GSH, which in turn may lead to increased levels of HNE [31,32]. On the other hand, S-adenosyl methionine (SAM) diminishes HNE modification of enzymes which have a vital role in the detoxification of HNE [32].…”
Section: Hne Reactivity and Metabolismmentioning
confidence: 99%
“…148 Another potential new biomarker is the mitochondrial protein, 149 carbomoyl phosphate synthetase 1 (CPS1). This protein level 150 increases faster than aspartate transaminanse (AST) and ALT 151 within the first 3 h after APAP ingestion[18,19]. CYPS1 levels were elevated after APAP treatment in mouse and human blood, as well 153 as in hepatocytes culture medium.…”
mentioning
confidence: 99%
“…The present results demonstrated that baicalein prevented liver injury induced by cisplatin. Oxidative stress causes oxidative damage and has been involved in the pathogenesis of many hepatotoxininduced liver injuries [21][22][23]. Under normal conditions, the body maintains a dynamic equilibrium between the production and detoxification of free radicals via the antioxidant defence system in the body.…”
Section: Resultsmentioning
confidence: 99%